Enhanced self-harm presentation reporting using additional ICD-10 codes and free text in NSW emergency departments - Grant E Sara; Jianyun Wu (Sax Institute, 2023)
Objectives: Understanding and responding to emergency department (ED) presentations for suicide and self-harm is a major health system priority. Reporting using routinely collected ED diagnoses or presenting problem codes leads to significant underestimation of rates. We aimed to implement an enhanced method for reporting ED self-harm presentations in New South Wales (NSW), Australia. Methods: An enhanced method was developed based on a literature review and clinical consultation. For NSW ED data collection records from 2005-2020, presenting problem codes were mapped to International Classification of Diseases version 10 (ICD-10). Self-harm codes (ICD-10 X60-84, Y87.0) were combined with additional codes for poisoning with medications commonly used in overdose and automated keyword searching of presenting problem text. Enhanced ED diagnoses were validated against hospital diagnoses for presentations resulting in hospital admission. Results & Discussion: Core ICD-10 self-harm codes identified 21 797 suicide and self-harm-related presentations per year to NSW EDs, of which 79% were for suicide-related ideation (R45.81). The enhanced method increased estimated annual presentations to 51 822 and increased sensitivity for suicide-related behaviours from 12.2% to 73.9%, while retaining high specificity (99.4%). Results matched known demographics of ED self-harm, and revised estimates were consistent with population rates reported by other jurisdictions. Service feedback and data sharing during the coronavirus disease 2019 (COVID-19) pandemic suggest that estimates from the enhanced method are plausible and sensitive to change. Conclusions: In NSW ED data, standard presenting problem codes recorded by clinicians detect less than half of presentations for self-harm or suicidal ideas. An enhanced method using additional codes and free text searching is computationally simple and increases sensitivity for monitoring trends and service performance. The method will continue to be refined as new data items become available.